Association between dietary calcium and depression among American adults: National health and nutrition examination survey - Shen, Xia; Gu, Xue; Liu, Yuan-Yuan; Yang, Long; Zheng, Meng; Jiang, Lei (Frontiers in Nutrition, 2023)
Background There is only limited evidence for an association between calcium and depression, and the relationship was inconsistent. Therefore, the aim of this study was to assess the relationship between dietary calcium and the risk of depressive symptoms in individuals over the age of 18 in the US. Methods We extracted 14971 participants from the US National Health and Nutrition Examination Survey (NHANES) 2007 to 2016 to probe their associations. Dietary calcium intake was measured through 24h dietary recall method. Patients with the Patient Health Questionnaire-9 (PHQ-9) ≥ 10 scores were believed to have depressive symptoms. The association between dietary calcium and depressive symptoms was investigated using multivariate logistic regression, sensitivity analysis, and restricted cubic spline regression. Results In this study, 7.6% (1144 / 14971) of them had depressive symptoms. After adjusting for sex, age, race, Poverty to income ratio, marital status, education, Body mass index, caffeine intake, carbohydrates intake, total energy intake, smoking status, alcohol consumption, physical activity, diabetes, hypertension, severe cardiovascular disease, cancer, serum vitamin D, serum calcium and calcium supplement, the adjusted ORs value (95% confidence interval) of depression for the lowest category (Q1 ≤ 534 mg/day) vs Q2-Q4 of calcium intake were 0.83(0.69-0.99), 0.97(0.65-0.95), and 0.80(0.63-0.98) with the p for trend (p = 0.014). The relationship between dietary calcium intake and depressive symptoms was Linear (non-linear p = 0.148). None of the interactions were significant except among races (p for interaction = 0.001). Conclusion Association between dietary calcium and the prevalence of depressive symptoms in US adults. And calcium intake was negatively associated with the risk of depressive symptoms. As calcium intake increased, the prevalence of depressive symptoms decreased.